Private Health Insurance History, Politics and Performance - Thomson, Sarah; Sagan, Anna; Mossialos, Elias (Social Sciences, 2020)
A collection of comparative case studies analysing the history, politics and performance of private health insurance globally and its implications for universal health coverage. This is essential reading for graduate students, scholars and policy makers working on health systems financing worldwide.